The new economy and economic growth in transition economies: The relevance of institutional infrastructure - Marcin Piatkowski (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The contribution of the `new economy' to economic growth in developing countries has so far been minimal. Despite the recent hype, the `old economy' will for long be the fundamental force behind economic growth in transition economies. Nonetheless, in the longer run the `new economy' offers great potential for faster economic growth in postsocialist economies. Realizing this potential is however not automatic. It can be left unharnessed if there is no suitable institutional infrastructure, which would allow for adoption, diffusion, and productive use of information and communication technologies (ICT). The paper constructs a New Economy Indicator (NEI) measuring the level of preparedness of transition economies for harnessing the potential of ICT to accelerate the long-term economic growth and catching-up with developed countries. In the NEI ranking Slovenia scored the highest, followed by the Czech Republic and Hungary. Albania, Bosnia and Herzegovina, and FR Yugoslavia occupy the bottom of the table. Similarity of the NEI results with the Global Competitiveness Report 2001 suggests that fundamentals responsible for the development of both the `new' and the `old' economy are largely the same. Hence, there is no `new' or `old' economy: there is only one economy where old recipes for development still apply.
Keywords: O1; O2; O3; O5; 330; post-communist transition; new economy; ICT; economic growth; Informationstechnik; Wirtschaftswachstum; Osteuropa; New Economy